2010
DOI: 10.1016/j.peptides.2010.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Human adrenomedullin and its binding protein ameliorate sepsis-induced organ injury and mortality in jaundiced rats

Abstract: Sepsis is a serious complication for patients with obstructive jaundice. Although administration of adrenomedullin (AM) in combination with its binding protein (AMBP-1) is protective after injury, it remains unknown whether AM/AMBP-1 ameliorates sepsis-induced organ injury and mortality in the setting of biliary obstruction. The aim of this study is, therefore, to test the efficacy of human AM/AMBP-1 in a rat model of obstructive jaundice and polymicrobial sepsis. To study this, obstructive jaundice was induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Note that in these survival experiments, treatment was started 5 h after CLP surgery. Other studies have also demonstrated beneficial effects coadministration of ADM and AMBP-1 in models of hemorrhagic shock ( 140 142 ), ischemia/reperfusion ( 143 , 144 ), endotoxemia ( 98 ), and septic shock ( 145 , 146 ). To what extent complement factor H influences the described ADM-mediated effects remains unclear as the majority of preclinical studies on ADM with AMBP-1 coadministration did not compare ADM/AMBP-1 with ADM alone.…”
Section: Adm and Adm-targeted Therapy As Treatment Strategies Relevanmentioning
confidence: 93%
“…Note that in these survival experiments, treatment was started 5 h after CLP surgery. Other studies have also demonstrated beneficial effects coadministration of ADM and AMBP-1 in models of hemorrhagic shock ( 140 142 ), ischemia/reperfusion ( 143 , 144 ), endotoxemia ( 98 ), and septic shock ( 145 , 146 ). To what extent complement factor H influences the described ADM-mediated effects remains unclear as the majority of preclinical studies on ADM with AMBP-1 coadministration did not compare ADM/AMBP-1 with ADM alone.…”
Section: Adm and Adm-targeted Therapy As Treatment Strategies Relevanmentioning
confidence: 93%
“…The effects of AM are mediated by the functional receptor combination of calcitonin receptor-like receptor with receptor activity-modifying protein-2 or -3 [134]. Our group recently revealed that the small intestine is a major source of AM during CLP-induced polymicrobial sepsis in rats, which may account for the increased portal blood flow observed in the early stage of sepsis [69].…”
Section: Am and Ambp-1mentioning
confidence: 99%
“…Recently, the understanding of the regulation of AM activity in sepsis has been greatly expanded after the discovery of AMBP-1 in mammalian blood [69,70]. Inflammatory cytokines, particularly IFN-␥, have been recognized as positive regulators of AMBP-1 expression, whereas oxidative stress and NF-B-sensitive microRNA-146a have been shown to down-regulate AMBP-1 [135,136].…”
Section: Am and Ambp-1mentioning
confidence: 99%
“…Target sites comprise the cardiorespiratory organs and immune cells . Adrenomedullin has been shown to be anti‐inflammatory in animal models of sepsis, pancreatitis, arthritis and colonic inflammation . Adrenomedullin was also reported to inhibit cell proliferation and inflammatory mediator secretion by synovial fibroblasts of rheumatoid arthritis patients .…”
Section: Anti‐inflammatory Neuropeptidesmentioning
confidence: 99%
“…Target sites comprise the cardiorespiratory organs and immune cells [116]. Adrenomedullin has been shown to be anti-inflammatory in animal models of sepsis, pancreatitis, arthritis and colonic inflammation [117][118][119][120].…”
Section: Adrenomedullinmentioning
confidence: 99%